Interactive Construction and Animation of Layered Elastically Deformable Characters - Turner, Russell; Gobbetti, Enrico (Computer graphics forum, 1998)
An interactive system is described for creating and animating deformable 3D characters. By using a hybrid layered model of kinematic and physics‐based components together with an immersive 3D direct manipulation interface, it is possible to quickly construct characters that deform naturally when animated and whose behavior can be controlled interactively using intuitive parameters. In this layered construction technique, called the elastic surface layer model, a simulated elastically deformable skin surface is wrapped around a kinematic articulated figure. Unlike previous layered models, the skin is free to slide along the underlying surface layers constrained by geometric constraints which push the surface out and spring forces which pull the surface in to the underlying layers. By tuning the parameters of the physics‐based model, a variety of surface shapes and behaviors can be obtained such as more realistic‐looking skin deformation at the joints, skin sliding over muscles, and dynamic effects such as squash‐and‐stretch and follow‐through. Since the elastic model derives all of its input forces from the underlying articulated figure, the animator may specify all of the physical properties of the character once, during the initial character design process, after which a complete animation sequence can be created using a traditional skeleton animation technique. Character construction and animation are done using a 3D user interface based on two‐handed manipulation registered with head‐tracked stereo viewing. In our configuration, a six degree‐of‐freedom head‐tracker and CrystalEyes shutter glasses are used to display stereo images on a workstation monitor that dynamically follow the user head motion. 3D virtual objects can be made to appear at a fixed location in physical space which the user may view from different angles by moving his head. To construct 3D animated characters, the user interacts with the simulated environment using both hands simultaneously: the left hand, controlling a Spaceball, is used for 3D navigation and object movement, while the right hand, holding a 3D mouse, is used to manipulate through a virtual tool metaphor the objects appearing in front of the screen. Hand‐eye coordination is made possible by registering virtual space to physical space, allowing a variety of complex 3D tasks necessary for constructing 3D animated characters to be performed more easily and more rapidly than is possible using traditional interactive techniques.